2015
DOI: 10.5539/ies.v8n4p23
|View full text |Cite
|
Sign up to set email alerts
|

Connection of Environmental Education with Application of Experiential Teaching Methods: A Case Study from Greece

Abstract: The main objective of this case study is to examine secondary education teachers' opinions concerning the connection of environmental education with the use of experiential teaching methods. Exploring whether the application of experiential methods can upgrade the learning procedure, leading to a more holistic approach, the research focuses on certain aspects of today's educational reality in the field of secondary environmental education. Studying a sample of secondary education teachers in Northern Greece, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
15
0
5
Order By: Relevance
“…Before the students participated in the teleconferences, they had in-class familiarisation sessions in the workshop, which lasted for 3 hours, as well as a pilot teleconference in the workshop in order to experiment on the use of the platform and its tools, the participation and the use of experiential techniques. Experiential learning is a process based on the pedagogical principle of learning by doing as students acquire knowledge after having experienced or done something new (Koutsoukos, Fragoulis, & Valkanos, 2015). Experiential techniques can go beyond traditional lecture and transfer of information can actively engage students making the learning procedure more interesting and appealing (Maloof, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Before the students participated in the teleconferences, they had in-class familiarisation sessions in the workshop, which lasted for 3 hours, as well as a pilot teleconference in the workshop in order to experiment on the use of the platform and its tools, the participation and the use of experiential techniques. Experiential learning is a process based on the pedagogical principle of learning by doing as students acquire knowledge after having experienced or done something new (Koutsoukos, Fragoulis, & Valkanos, 2015). Experiential techniques can go beyond traditional lecture and transfer of information can actively engage students making the learning procedure more interesting and appealing (Maloof, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Also and connectedly, according to the attitudes expressed by the majority of the sample, the learning process needs to be enriched with innovative teaching practices, such as the pedagogic use of ICT, as it increases students' interest and motivation. It is worth noting that a research study with a sample of 157 teachers of Secondary Education from General and Technical-Vocational High Schools in the prefecture of Central Macedonia also showed that the majority believe that innovative teaching practices, such as experiential teaching methods can have beneficial outcomes, especially as regards environmental education (Koutsoukos, Fragoulis and Valkanos, 2015). The research findings show that the English teachers who participated in the study actually believe that it is their responsibility to provide a learning environment that increases student motivation and helps them develop independent learning.…”
Section: Discussionmentioning
confidence: 99%
“…H τεχνική της προσομοίωσης εξυπηρετεί σε πολύ μεγάλο βαθμό τη μαθησιακή εξ αποστάσεως διαδικασία καθώς ενισχύει τη συμμετοχή και την καλύτερη επεξεργασία του γνωστικού αντικειμένου από την ομάδα. Η εφαρμογή της θεωρίας στην πράξη και μάλιστα με τη μέθοδο της προσομοίωσης δημιουργεί περισσότερο ενδιαφέρον, γίνεται πιο "απτή" και κατανοητή και προσφέρει καλύτερα μαθησιακά αποτελέσματα στους εκπαιδευόμενους (Koutsoukos, Fragoulis, & Valkanos, 2015). Προκαλεί γόνιμες απορίες και προβληματισμούς στους εκπαιδευόμενους και συμβάλλει μέσω της ανακαλυπτικής μάθησης στην επίτευξη των μαθησιακών στόχων.…”
Section: τηλεδιάσκεψηunclassified